The PROSIT tool: Toward the optimal design of probabilistic soft real‐time systems. (10th July 2018) - Villalba Frías, Bernardo; Palopoli, Luigi; Abeni, Luca; Fontanelli, Daniele
Summary: In recent years, series of important achievements have paved the way for the introduction of probabilistic analysis in the area of soft real‐time systems design. In this article, we present an extensible design tool, called PROSIT, which facilitates the access to this technology for a potentially large number of researchers and industrial practitioners. The tool enables the probabilistic analysis of the temporal performance of a real‐time task under fixed‐priority and resource reservations scheduling algorithms. For resource reservations, the tool also offers an automatic procedure for the synthesis of scheduling parameters that optimize a quality metric related to the probabilistic behavior of the tasks.